Idosos diabéticos: acompanhamento de um grupo de diabéticos em uma Unidade Básica de Saúde - Fernandes, Jéssia Oliveira dos Santos (2007)
The education in diabetes is indispensable part of the patient's treatment, associate to the appropriate metabolic control, to the physical activity and the diet. The largest knowledge level on the disease and their complications are related the an improvement of the life quality, with reduction of the number of hypoglycemic crises, smaller number of internments hospital's, better metabolic control and larger acceptance of the disease. Like this, the objective of this research is to analyze the diabetic seniors' participation in education groups and control in a Basic Unit of the Program health of the Family. It was used to drive this study the descriptive research with quanti-qualitative approach, for considering that this method allows better understanding diabetic, so much in his/her complexity and specificity as in relation to the valorization in the autocare. The obtained results demonstrated that the diabetic seniors are among 60 to 79 years (73%), with female predominance (60%), 72% don't have knowledge of the existence of a group control and education in the basic unit that you/they frequent, (33%) they refer to participate more than 12 years in the group the, (83%) of those researched they know the disease, 58% get to maintain stable the glycemic, 59% referred other reasons for us not to check the glycemic, 93% answered that you/they make use do use of medication hypoglycemic, 65% of those researched don't participate in physical activities in group, 64% control the diabetes through the diet, 93% of those researched attend the consultations scheduling, 82% of those researched don't attend the group meetings controls accomplished by UBS, 86%, they understand and they follow the orientations for the control of the diabetes, 60% of those researched participate in the meetings in the group for us to learn more on the disease, 64% like more of receiving orientations, and 57% of the interviewees suggested the accomplishment of lectures explaining more on the disease. It is ended like this that is necessary that there are invigoration and enlargement of the education group in diabetes, in referred UBS, with views to motivate the patient and his/her family announce her indeed of him, through which you/they can elaborate and to solve the current problems of the diabetes